2022
DOI: 10.3389/fmicb.2022.845173
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biosynthesis of Fatty Acids Contributes to Ciprofloxacin Resistance in Pseudomonas aeruginosa

Abstract: Antibiotic-resistant Pseudomonas aeruginosa is insensitive to antibiotics and difficult to deal with. An understanding of the resistance mechanisms is required for the control of the pathogen. In this study, gas chromatography–mass spectrometer (GC-MS)-based metabolomics was performed to identify differential metabolomes in ciprofloxacin (CIP)-resistant P. aeruginosa strains that originated from P. aeruginosa ATCC 27853 and had minimum inhibitory concentrations (MICs) that were 16-, 64-, and 128-fold (PA-R16CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…It is also involved in the elimination of cellular metabolic byproducts. L-carnitine is involved in regulating stress responses, energy metabolism, and protein folding, irrespective of whether bacteria inhabit aerobic or anaerobic environments [ 46 ]. An important function of L-carnitine is its ability to mitigate osmotic stress in bacteria by acting as an osmolyte, thus helping maintain cellular fluid levels and preventing cellular damage [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also involved in the elimination of cellular metabolic byproducts. L-carnitine is involved in regulating stress responses, energy metabolism, and protein folding, irrespective of whether bacteria inhabit aerobic or anaerobic environments [ 46 ]. An important function of L-carnitine is its ability to mitigate osmotic stress in bacteria by acting as an osmolyte, thus helping maintain cellular fluid levels and preventing cellular damage [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of CF, pulmonary biomarkers are increasingly employed to examine disease action and assess the response to therapy in individuals [95]. Recently, Su et al [96] conducted research indicating that an increased biosynthesis of fatty acids plays a crucial role in CFX resistance development in P. aeruginosa. Their study revealed that the elevated fatty acid formation is a distinctive property of metabolomes resistant to CFX, augmented by heightened gene expression and enzymatic action within the biochemical network.…”
Section: Potential Biomarkers For Identifying Cfx Resistance In Lrtismentioning
confidence: 99%
“…These findings underscore the significance of increased fatty acid biosynthesis in the CFX resistance of P. aeruginosa, offering a potential target cascade for addressing CFX-resistant strains of the bacteria. The discovery of novel biomarkers is inevitable for enhancing the remedy of CF in patients [96].…”
Section: Potential Biomarkers For Identifying Cfx Resistance In Lrtismentioning
confidence: 99%